Role and mechanism of the maturation cleavage of VP0 in poliovirus assembly: structure of the empty capsid assembly intermediate at 2.9 A resolution. - Basavappa, R. (Cold Spring Harbor Laboratory Press, 1994)
The crystal structure of the P1/Mahoney poliovirus empty capsid has been determined at 2.9 A resolution. The empty capsids differ from mature virions in that they lack the viral RNA and have yet to undergo a stabilizing maturation cleavage of VP0 to yield the mature capsid proteins VP4 and VP2. The outer surface and the bulk of the protein shell are very similar to those of the mature virion. The major differences between the 2 structures are focused in a network formed by the N-terminal extensions of the capsid proteins on the inner surface of the shell. In the empty capsids, the entire N-terminal extension of VP1, as well as portions corresponding to VP4 and the N-terminal extension of VP2, are disordered, and many stabilizing interactions that are present in the mature virion are missing. In the empty capsid, the VP0 scissile bond is located some 20 A away from the positions in the mature virion of the termini generated by VP0 cleavage. The scissile bond is located on the rim of a trefoil-shaped depression in the inner surface of the shell that is highly reminiscent of an RNA binding site in bean pod mottle virus. The structure suggests plausible (and ultimately testable) models for the initiation of encapsidation, for the RNA-dependent autocatalytic cleavage of VP0, and for the role of the cleavage in establishing the ordered N-terminal network and in generating stable virions.